Applying the Passivhaus standard to a terraced house in a hot and humid tropical climate – Evaluation of comfort and energy performance. (May 2020) - Sigalingging, Roy Candra; Chow, David; Sharples, Steve
In a hot and humid tropical climate, natural ventilation brings high levels of moisture into dwellings that, together with occupant activity, can result in very elevated internal relative humidity levels. Coupling these high relative humidities with high internal air temperatures creates occupant thermal discomfort, which is typically ameliorated in the tropics using energy-intensive air conditioning systems. This paper has investigated the potential benefits for thermal comfort and energy usage of applying the German Passivhaus standard to tropical dwellings. By creating a super insulated and air-tight envelope, the Passivhaus standard reduces fabric heat transfer, controls air infiltration and provides low-energy comfort. Applying this approach to a tropical terraced house might be effective but could, potentially, have an adverse impact on mechanical cooling demand. This study took an actual terraced property in Jakarta, Indonesia and thermally modelled its performance as insulation and airtightness levels were incrementally improved up to the Passivhaus standard. Field measurements in the dwelling of air temperature and relative humidity were used to validate the thermal model of the existing house. The validated model then tested the feasibility of meeting the Passivhaus energy standard for cooling in the modified tropical house. Simulation allowed the effects of air conditioning (AC) and dehumidifiers on thermal comfort and cooling loads to be investigated. The research develop the Passivhaus building model that had the floor insulation removed to let the ground floor act as a thermal sink and potentially provide radiant cooling. Analysis revealed that the building's predicted air temperatures were affected in a beneficial way by having the Passivhaus without floor insulation. Practical application: Cooling in hot and humid tropical region is an energy-intensive approach. Design approaches that can bring comfort and save energy for the occupant are essential. The success of Passivhaus standard in mild climate might be transferable to bring comfort in tropical housing. Best practice can be developed by analysing the Passivhaus building performance in hot and humid tropical region.